Rapid reorganization of the Milan metropolitan public safety answering point operations during the initial phase of the COVID‐19 outbreak in Italy. Issue 6 (27th September 2020) - Marrazzo, Francesco; Spina, Stefano; Pepe, Paul E.; D'Ambrosio, Annapaola; Bernasconi, Filippo; Manzoni, Paola; Graci, Carmela; Frigerio, Cristina; Sacchi, Marco; Stucchi, Riccardo; Teruzzi, Mario; Baraldi, Sara; et al.
Abstract: Objective: To quantify how the first public announcement of confirmed coronavirus disease 2019 (COVID‐19) in Italy affected a metropolitan region's emergency medical services (EMS) call volume and how rapid introduction of alternative procedures at the public safety answering point (PSAP) managed system resources. Methods: PSAP processes were modified over several days including (1) referral of non‐ill callers to public health information call centers; (2) algorithms for detection, isolation, or hospitalization of suspected COVID‐19 patients; and (3) specialized medical teams sent to the PSAP for triage and case management, including ambulance dispatches or alternative dispositions. Call volumes, ambulance dispatches, and response intervals for the 2 weeks after announcement were compared to 2017–2019 data and the week before. Results: For 2 weeks following outbreak announcement, the primary‐level PSAP (police/fire/EMS) averaged 56% more daily calls compared to prior years and recorded 9281 (106% increase) on Day 4, averaging ∼400/hour. The secondary‐level (EMS) PSAP recorded an analogous 63% increase with 3863 calls (∼161/hour; 264% increase) on Day 3. The COVID‐19 response team processed the more complex cases (n = 5361), averaging 432 ± 110 daily (∼one‐fifth of EMS calls). Although community COVID‐19 cases increased exponentially, ambulance response intervals and dispatches (averaging 1120 ± 46 daily) were successfully contained, particularly compared with the week before (1174 ± 40; P = 0.02). Conclusion: With sudden escalating EMS call volumes, rapid reorganization of dispatch operations using tailored algorithms and specially assigned personnel can protect EMS system resources by optimizing patient dispositions, controlling ambulance allocations and mitigating hospital impact. Prudent population‐based disaster planning should strongly consider pre‐establishing similar highly coordinated medical taskforce contingencies.